2016
DOI: 10.2341/15-154-l
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Load and Phase Transformation of Monolithic Zirconia Crowns Submitted to Different Aging Protocols

Abstract: Monolithic zirconia crowns have many favorable properties and may potentially be used to solve dental problems such as chipping. However, monolithic zirconia crown resistance can be affected by its phase transformation when subjected to low temperatures, humidity, and stress. This study evaluated the fracture load and phase transformation of monolithic zirconia crowns submitted to different thermal and mechanical aging tests. Seventy monolithic zirconia crowns were randomly divided into the following five grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
(70 reference statements)
0
31
0
2
Order By: Relevance
“…18 This study showed Weibull modulus ranging from 10 to 21.43 (Table; Figure 3), which is consistent with the values reported for ceramic crowns. 14,25 We noticed a tendency for Weibull modulus increase after aging, since the groups with higher m-phase content tended to present higher Weibull modulus, which probably can be explained by the toughening mechanism that closes the crack tip, avoiding crack growth. In addition, a small difference in strength between specimens with large flaws and small flaws was observed, probably because of the rising of the toughness curve, which leads to higher toughness for larger flaws and lower toughness for smaller flaws.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…18 This study showed Weibull modulus ranging from 10 to 21.43 (Table; Figure 3), which is consistent with the values reported for ceramic crowns. 14,25 We noticed a tendency for Weibull modulus increase after aging, since the groups with higher m-phase content tended to present higher Weibull modulus, which probably can be explained by the toughening mechanism that closes the crack tip, avoiding crack growth. In addition, a small difference in strength between specimens with large flaws and small flaws was observed, probably because of the rising of the toughness curve, which leads to higher toughness for larger flaws and lower toughness for smaller flaws.…”
Section: Discussionmentioning
confidence: 96%
“…5,6,12,14,23,24 Pereira and collaborators 8 stated that the critical point of m-phase content for a deleterious effect on mechanical performance should be above 50%. Our data show that the AUT+MechLoad group, even with 60% m-phase content, had a statistically higher characteristic strength than the as-sintered condition.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure in Y‐TZP may change from tetragonal to monoclinic due to aging or mechanical stress . The amount of monoclinic phase in Y‐TZP increases with aging . With two phases present in Y‐TZP, light scattering might increase .…”
Section: Discussionmentioning
confidence: 99%
“…23,24,35,36 The amount of monoclinic phase in Y-TZP increases with aging. 24,35,37,38 With two phases present in Y-TZP, light scattering might increase. 18 The monoclinic and tetragonal crystals have different optical properties, which can influence the opacity.…”
Section: Discussionmentioning
confidence: 99%
“…Фазовый переход наблюдался на всех поверхностях коронки и во всех группах образцов, прошедших термическую, механическую или термомеханическую обработку (от 1,9 до 8,9%). Монолитные коронки обладали очень высокой прочностью разрушения, структурной надежностью и хорошей стабильностью (после любого из циклов испытаний количество моноклинной фазы было незначительным) [6].…”
Section: лабораторные испытания с проведением искусственного термичесunclassified